Oral fibroblasts rescue osteogenic differentiation of mesenchymal stem cells after exposure to Zoledronic acid in a paracrine effect - Berg, Tal; Doppelt-Flikshtain, Ofri; Coyac, Benjamin R.; Zigdon-Giladi, Hadar (Frontiers in Pharmacology, 2023)
Background: Medication-related osteonecrosis of the jaw is a serious complication that develops in oncologic patients treated with zoledronic acid. Although used for over thirty years, the influence of zoledronic acid on bone has been thoroughly investigated, mainly on osteoclasts. While decreasing osteoclast differentiation and function, for many years it was thought that zoledronic acid increased osteoblast differentiation, thus increasing bone volume. Moreover, despite the influence of soft tissue on the bone healing process, the impact of zoledronic acid on the interaction between soft tissue and bone was not investigated. Aim Our goal was to investigate the influence of Zoledronic Acid and soft tissue cells on osteogenic differentiation of mesenchymal stem cells (MSCs). Materials and methods Osteogenic differentiation of MSCs was examined after exposure to Zoledronic Acid. To determine the influence of soft tissue cells on MSCs’ osteogenic differentiation, conditioned media from keratinocytes and oral fibroblasts were added to osteogenic medium supplemented with Zoledronic Acid. Proteomic composition of keratinocytes' and fibroblasts' conditioned media were analyzed. Results Zoledronic Acid decreased osteogenic differentiation of MSCs by seven-fold. The osteogenic differentiation of MSCs was restored by the supplementation of fibroblasts’ conditioned medium to osteogenic medium, despite Zoledronic acid treatment. Five osteogenic proteins involved in the TGFβ pathway were exclusively identified in fibroblasts’ conditioned medium, suggesting their role in the rescue effect. Conclusions Oral fibroblasts secrete proteins that enable osteogenic differentiation of MSCs in the presence of Zoledronic Acid.